The Magnetocaloric Composite Designed by Multi‐Gd‐Al‐Co Microwires with Close Performances. Issue 16 (15th May 2019) - Shen, Hongxian; Luo, Lin; Xing, Dawei; Jiang, Sida; Liu, Jingshun; Huang, Yongjiang; Guo, Shu; Sun, Haichao; Liu, Yanfen; Sun, Jianfei; Phan, Manh‐Huong
Abstract : A new magnetocaloric composite composed of three types of soft ferromagnetic Gd‐based microwires with equal mass ratio and close magnetocaloric performances is designed. The Curie temperatures ( T C ) of these three wires are ≈97, ≈100, and ≈101 K, respectively. However, the magnetization versus temperature curve of the composite sample shows almost a single ferromagnetic–paramagnetic transition at ≈97 K. For a field change of µ0 Δ H  = 5 T, the maximum entropy change ( − Δ S M max ) and refrigerant capacity (RC) of this composite are calculated to be ≈9.98 J kg −1  K −1 and ≈665 J kg −1, respectively. There is a good agreement between the calculated −Δ S M ( T ) curve and the experimental data, indicating weak magnetic interactions among different wire compositions. Additionally, the calculated universal master curves of the composite and its Gd‐Al‐Co components are fitted very well, which reveals the second‐order type of the magnetic transition for the composite. The designed composite integrates all magnetocaloric properties of its components, suggesting that the Gd‐based amorphous wires with close magnetocaloric properties can be designed as an excellent refrigerant for use in active magnetic refrigerators. Abstract : A new magnetocaloric composite is designed using three types of soft ferromagnetic Gd‐based microwires with close Curie temperatures and magnetocaloric effects. The composite shows a single ferromagnetic–paramagnetic transition occurred near ≈97 K. The maximum entropy change and refrigerant capacity of this composite are calculated to be ≈9.98 J kg −1  K −1 and ≈665 J kg −1, respectively.